IDIOPATHIC GRANULOMATOUS MASTITIS: CASE SERIES - Fontinele, Danilo Rafael da Silva; Siqueira, Laís Neiva Rego; Vieira, Sabas Carlos; Santos, Lina Gomes dos (Mastology, 2019)
Idiopathic granulomatous mastitis is a rare disease that mimics other pathological conditions, including breast adenocarcinoma, breast tuberculosis, and abscess. Three patients diagnosed with idiopathic granulomatous mastitis were analyzed, receiving corticosteroid treatment, antibiotic therapy in cases of abscesses, and, in one case, resection of the affected breast segment. All patients exhibited regression of symptoms.